PENGARUH KEPERCAYAAN SISWA PADA MATEMATIKATERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA - AMINULLAH AMINULLAH (GANEC SWARA, 2020)
This study aims to describe the effect of student confidence in mathematics on critical thinking skills and student learning outcomes. This research is a quasi-experimental study, the sample in this study is X class students majoring in hotel accommodation as many as 30 students. Retrieval of data using questionnaire and test instruments. The results of this study indicate that the average student confidence in mathematics is 58.06 with a standard deviation of 3.65. While the ability to think critically and student learning outcomes obtained an average of 56.94 with a standard deviation of 9.63. The influence of students' trust in mathematics on critical thinking skills and student learning outcomes have a positive effect shown by F arithmetic (4,485) ≥ F table (4.18) or the significance number in ANOVA 0.043 ≤ 0.05. The magnitude of the effect of students' trust in mathematics on critical thinking skills and student learning outcomes of 13.4%. The regression equation obtained by Y ̂ = 0.866 + 0.966X + ϵ. This means that if the value of students' trust in mathematics is 1 unit, the value of the predicted variable will increase by 0.966. The higher the student's confidence in mathematics, the ability to think critically and student learning outcomes will also increase.